Detection of PTFE microparticles by ICP-qMS operated in single-particle mode. Issue 11 (11th October 2022) - Gelman, Faina; Muszyńska, Magdalena; Karasiński, Jakub; Lev, Ovadia; Halicz, Ludwik
Abstract : In this study, we examine the possibility of detecting PTFE microparticles by ICP-qMS equipped with O2 dynamic reaction cell (DRC) and operated in single-particle mode. Abstract : In this study, we examine the possibility of the selective detection of PTFE microparticles by ICP-qMS equipped with O2 dynamic reaction cell (DRC) and operated in single-particle mode. Our analytical method is based on the earlier proposed approach for fluorine detection by ICP-MS/MS through the formation of BaF + ions ( m / z 157) in the plasma. Using microseconds dwell time the single-particle BaF + spikes with signal intensities significantly higher than the background were detected in the samples containing PTFE microparticles. Under the applied operating parameters, PTFE particles larger than 0.93 μm can be detected. The limit of detection of 8.5 × 10 5 particles per L was achieved for an acquisition time of 100 seconds. The most frequent particle diameter of 1.2 ± 0.1 μm determined by SP-ICP-MS analysis is consistent with the average diameter of 1.2 ± 0.2 μm, detected by DLS.